Public mobile wideband networks interference impact assessment on railways GSM-R network - Rouco, André (2022)
This paper presents a field study relating to the impact that public operator cellular networks such as UMTS (Universal Mobile Telecommunication System), LTE (Long-Term Evolution), and 5G-NR (5G - New Radio) have on railway GSM-R (Global System for Mobile Communications – Railway) networks. The validation of the interference calculation relied on actual network measurements taken along railway lines using a dedicated probe. Emissions from public networks, in some scenarios, have been shown to affect GSM-R networks to a large extent. The developed algorithm is currently being used in real GSM-R network planning to mitigate this negative effect on base station coverage and service performance.